Glial and neuronal expression of the Inward Rectifying Potassium Channel Kir7.1 in the adult mouse brain. Issue 5 (15th July 2019) - Papanikolaou, Maria; Lewis, Anthony; Butt, Arthur M.
Abstract: Inward Rectifying Potassium channels (Kir) are a large family of ion channels that play key roles in ion homeostasis and neuronal excitability. The most recently described Kir subtype is Kir7.1, which is known as a K + transporting subtype. Earlier studies localised Kir7.1 to subpopulations of neurones in the brain. However, the pattern of Kir7.1 expression across the brain has not previously been examined. Here, we have determined neuronal and glial expression of Kir7.1 in the adult mouse brain, using immunohistochemistry and transgenic mouse lines expressing reporters specific for astrocytes [glial fibrillary acidic protein‐enhanced green fluorescent protein (GFAP‐EGFP], myelinating oligodendrocytes (PLP‐DsRed), oligodendrocyte progenitor cells (OPC, Pdgfra‐cre ER T 2 / Rosa26‐YFP double‐transgenic mice) and all oligodendrocyte lineage cells (SOX10‐EGFP). The results demonstrate significant neuronal Kir7.1 immunostaining in the cortex, hippocampus, cerebellum and pons, as well as the striatum and hypothalamus. In addition, astrocytes are shown to be immunopositive for Kir7.1 throughout grey and white matter, with dense immunostaining on cell somata, primary processes and perivascular end‐feet. Immunostaining for Kir7.1 was observed in oligodendrocytes, myelin and OPCs throughout the brain, although immunostaining was heterogeneous. Neuronal and glial expression of Kir7.1 is confirmed using neurone‐glial cortical cultures and optic nerve glial cultures. Notably, Kir7.1 have been shown to regulate the excitability of thalamic neurones and our results indicate this may be a widespread function of Kir7.1 in neurones throughout the brain. Moreover, based on the function of Kir7.1 in multiple transporting epithelia, Kir7.1 are likely to play an equivalent role in the primary glial function of K + homeostasis. Our results indicate Kir7.1 are far more pervasive in the brain than previously recognised and have potential importance in regulating neuronal and glial function. Abstract : The key finding of this study is that Kir7.1 expression is widespread in the adult mouse brain in both neurones and glia ‐ astrocytes and oligodendrocytes. Kir7.1 are likely to play important roles in regulating neuronal excitability and glial K+ homeostasis.